The Crossroads of Philosophy: A Critical Reflection - Arnastya Iswara Sanantagraha, Arnastya Iswara Sanantagraha; Puspitaloka Mahadewi, Erlina (International Journal of Educational Research & Social Sciences, 2024)
Philosophy enriches and dynamizes a science in its development. The choice of a good philosophical system becomes an unproductive debate but is essential in gaining an understanding of the importance of developing a coherent and comprehensive framework of thought to understand social phenomena. This research is a scientific reflection on the question of the best choice of philosophical systems and the belief in the existence of absolute and relativistic philosophy. This scientific reflection uses a qualitative narrative method in a literature review to answer the research question. Based on the research results, the author sees that a philosophical system has a specificity in contributing to the field of life and science independently. The author also provides a review of answers to the choice of a philosophical system that is suitable for the Doctoral program in Computer Science, namely Information Systems. The answer to the existence of a coherent philosophical system that underlies human wisdom is presented by the author in this paper. This scientific reflection is expected to contribute to the science of knowledge, especially the philosophy of science and the application of research stages in the field of Computer Science. Further research needs to be done to obtain the accuracy of a philosophical system that is suitable for the research topic and other fields of science.